Differential response of sweet potato cultivars to cold storage - Araújo, Nícolas Oliveira de (2019)
Cold-induced sweetening (CIS) and chilling injury symptoms are the main physiological disorders that compromise the quality of sweet potato roots stored at suboptimal temperatures. The manifestation of chilling-induced physiological disorders depends on the temperature, time of exposure to the stress condition and chilling sensitivity level of the genotype. Therefore, the objective of this work was to describe differences in chilling sensitivity among sweet potato cultivar roots; evaluate the involvement of invertases and sucrose synthase in CIS; describe the impact of CIS on non-enzymatic darkening of sweet potato chips; and to evaluate the importance of the enzymatic and non-enzymatic antioxidant system in the presence or not of chilling injury symptoms in sweet potato roots. Sweet potato roots of the cultivars BRS Rubissol, BRS Cuia and Beauregard were stored at 6 or 13 °C for up to 60 days. The roots of the cultivar Beauregard showed higher chilling injury tolerance when compared to the cultivars BRS Rubissol and BRS Cuia. The CIS was shown at 6 °C due to the accumulation of non- reducing sugars, and the low invertase activity in the cultivars BRS Rubissol and BRS Cuia. On the other hand, the CIS in the Beauregard cultivar was characterized by the high invertase activity and the relatively equivalent accumulation amidst reducing and non-reducing sugars. Sucrose synthase activity was induced only in the cold-sensitive cultivars BRS Rubissol and BRS Cuia when stored at 6 °C, probably as an energy conservation mechanism. Non-enzymatic darkening of sweet potato chips was more influenced by the non-reducing sugar content when compared to reducing sugars. In contrast to the cultivars BRS Rubissol and BRS Cuia, the roots of the Beauregard cultivar did not exhibit symptoms of chilling injury by reducing oxidative stress at 6 °C through increased catalase and ascorbate peroxidase activities, as well as by increasing the content of carotenoids. Keywords: Ipomoea batatas. Invertases. Sucrose synthase. Sweetening. Chilling injury.